Gas physisorption measurements as a quality control tool for the properties of graphene/graphite powders - Marchesini, Sofia; Turner, Piers; Paton, Keith R.; Reed, Benjamen P.; Brennan, Barry; Koziol, Krzysztof K.; Pollard, Andrew J. (Elsevier, 2020)
The industrial-scale production and commercialisation of graphene and related 2D materials introduces the need for rapid, reliable and cost-effective quality control procedures. Currently, microscopy-based techniques are used to measure the lateral size and thickness of particles but while powerful, these techniques suffer from limitations such as lengthy analysis time, high costs and limited sampling. In the case of carbon-based 2D materials, as the stacking of multiple graphene sheets causes a reduction in the surface to mass ratio, the number of layers can hypothetically be calculated by comparing the theoretical surface area of monolayer graphene (2630 m2/g) to the calculated specific surface area (SSA) measured by gas physisorption measurements. However, despite the potential of this method of analysis, there is limited understanding regarding the characterisation of commercial graphene/graphite powders produced via bottom-up and top-down methods. Herein, the SSAs of a variety of commercially-available graphitic powders were measured using nitrogen physisorption isotherms at 77 K and applying Brunauer-Emmett-Teller theory. The as-obtained SSAs were then correlated to the structural and chemical properties of the materials (obtained using conventional techniques) to demonstrate the suitability of this measurement technique for quality control of graphitic powders
Keywords: Specific surface area; Nitrogen physisorption; Layers; 2D materials; Graphene